A study of the conditions that hinder the children in Azerbaijan schools from acquiring an adequate knowledge of and ability in Farsi - Dayhimi, Narsrullah 1925- (1963)
The factors and problems hindering the learning of the Farsi language in schools of Azerbaijan are investigated in this study. The questionnaire technique was chosen as the main tool for the investigation. It was found out that the pupils' general competency in the Farsi language is "poor" causing children to face several difficulties because of their inefficiency especially in subjects where communication and language is involved
Thesis (M.Ed.)--University of the Philippines
Keywords: Iranian languages -- Study and teaching